Histamine Produced by Gram-Negative Bacteria Impairs Neutrophil's Antimicrobial Response by Engaging the Histamine 2 Receptor - Karim Dib; Amal El Banna; Clara Radulescu; Guillermo Lopez Campos; Gerard Sheehan; Kevin Kavanagh (Karger Publishers, 2022)
We found that histamine (10−9 M) did not have any effect on the in vitro capture of Escherichia coli by neutrophils but accelerated its intracellular killing. In contrast, histamine (10−6 M) delayed the capture of Escherichia coli by neutrophils and reduced the amounts of pHrodo zymosan particles inside acidic mature phagosomes. Histamine acted through the H4R and the H2R, which are coupled to the Src family tyrosine kinases or the cAMP/protein kinase A pathway, respectively. The protein kinase A inhibitor H-89 abrogated the delay in bacterial capture induced by histamine (10−6 M) and the Src family tyrosine kinase inhibitor PP2 blocked histamine (10−9 M) induced acceleration of bacterial intracellular killing and tyrosine phosphorylation of proteins. To investigate the role of histamine in pathogenicity, we designed an Acinetobacter baumannii strain deficient in histamine production (hdc::TOPO). Galleria mellonella larvae inoculated with the wild-type Acinetobacter baumannii ATCC 17978 strain (1.1 × 105 CFU) died rapidly (100% death within 40 h) but not when inoculated with the Acinetobacter baumannii hdc::TOPO mutant (10% mortality). The concentration of histamine rose in the larval haemolymph upon inoculation of the wild type but not the Acinetobacter baumannii hdc::TOPO mutant, such concentration of histamine blocks the ability of hemocytes from Galleria mellonella to capture Candida albicans in vitro. Thus, bacteria-producing histamine, by maintaining high levels of histamine, may impair neutrophil phagocytosis by hijacking the H2R.